Deeply Located Cul-de-sac Uterine Leiomyoma Resulting in Severe Pelvic Pain - Agrawal, Ajay; Kuan-Gen, Huang (Nepal Journal of Obstetrics and Gynaecology, 2020)
A Cul-de sac FIGO Type 7 uterine myoma presenting with severe pelvic pain removed laparoscopically without significant blood loss and discharged on second day without complication. On follow up in one month she was free from pain. Though the location of uterine myoma can be unwieldy, laparoscopic myomectomy is feasible with patience and proper technique to give benefits of minimal invasive surgery to the patient. Keywords: laparoscopy, Myomectomy, Uterine Myoma